Hepatoprotective Effect of Olive and Argan Oils Supplemented with Tomato Lycopene in Wistar Rats - Aidoud, Aziouz; Elahcene, Omar; Ammouche, Ali; Rodriguez, Ana B. (Pakistan Journal of Nutrition, 2016)
Lycopene, the most important carotenoids, is a red lipophilic pigment containing 11 conjugated double bonds make lycopene a powerful radical scavenger. It has the powerful antioxidant activity within carotenoids and is an effective free radical scavenger. Virgin olive oil (VOO) and argan oil (AO) contain a wide variety of phytochemicals which are considered as a functional foods. The present study intended to assess the effect of various dietary VOO and AO in combination with lycopene consumption on some liver function parameters, including liver enzymes such as alanine amino-transferase (ALT), aspartate-aminotransferase (AST), alkaline phosphatase (ALP) as well as on hepatic lycopene concentration of wistar rats. Results showed that ingestion of VOO and AO diminished ALT, AST, ALP levels in all the groups assayed. The lycopen enrichment VOO and AO significantly improved the beneficial effects derived from the consumption of both oils on serum liver enzymes and protect the liver tissue by enhancing the hepatic lycopene concentration, induced hepatoprotective effect by ameliorating the capacity antioxidant and function parameters of the liver tissue in wistar rats. These results suggest that the inclusion of lycopene in VOO and AO may be used as a natural antioxidant to protect the liver against damage.